Hepatic transcriptome analyses of juvenile white bass (Morone chrysops) when fed diets where fish meal is partially or totally replaced by alternative protein sources - Fuller, S. Adam; Abernathy, Jason W.; Sankappa, Nithin Muliya; Beck, Benjamin H.; Rawles, Steven D.; Green, Bartholomew W.; Rosentrater, Kurt A.; McEntire, Matthew E.; Huskey, George; Webster, Carl D. (Frontiers in Physiology, 2024)
White bass (Morone chrysops) are a popular sportfish throughout the southern United States, and one parent of the commercially-successful hybrid striped bass (M. chrysops ♂ x M. saxatilis ♀). Currently, white bass are cultured using diets formulated for other carnivorous fish, such as largemouth bass (Micropterus salmoides) or hybrid striped bass and contain a significant percentage of marine fish meal. Since there are no studies regarding the utilization of alternative proteins in this species, we evaluated the global gene expression of white bass fed diets in which fish meal was partially or totally replaced by various combinations of soybean meal, poultry by-product meal, canola meal, soy protein concentrate, wheat gluten, or a commercial protein blend (Pro-Cision™). Six isonitrogenous (40% protein), isolipidic (11%), and isocaloric (17.1 kJ/g) diets were formulated to meet the known nutrient and energy requirements of largemouth bass and hybrid striped bass using nutrient availability data for most of the dietary ingredients. One of the test diets consisted exclusively of plant protein sources. Juvenile white bass (40.2 g initial weight) were stocked into a flow-through aquaculture system (3 tanks/diet; 10 fish/tank) and fed the test diets twice daily to satiation for 60 days. RNA sequencing and bioinformatic analyses revealed significant differentially expressed genes between all test diets when compared to fish meal control. A total of 1,260 differentially expressed genes were identified, with major ontology relating to cell cycle and metabolic processes as well as immune gene functions. This data will be useful as a resource for future refinements to moronid diet formulation, as marine fish meal becomes limiting and plant ingredients are increasingly added as a reliable protein source.